(untitled) (Dimensión Empresarial, 2019)
ABSTRACT This work focuses on the family business and its objective is to review the concept of family ness, specifically of family firm identity by teorizing as a first approach the way in which it is constructed from the integration of different theoretical lens such as the theory based on resources, the theory of organizactional identity and the organizational structuration rescued from the theory of transaction costs. The discussion revolves around the origins of a collective identity in organizations and in this case, as a way of differentiation between family businesses and those not being a family firm through logical propositions constructed from the review of relevant literature on the subject.